Analisis Manajemen Strategi Dalam Pengembangan Inovasi Pendidikan di MTs Persis 37 Sumedang - Sariah, Dedeh; Nugraha, Mulyawan Safwandy (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
This study examines strategic management in fostering educational innovations at MTs Persis 37 Sumedang, focusing on the leadership of the school principal. The research aims to describe the formulation, implementation, and evaluation of strategies for creative and innovative ideas. Using a qualitative descriptive approach, data were gathered through interviews and document analysis. The findings reveal that strategic formulation at MTs Persis 37 involves identifying external opportunities and threats, assessing internal strengths and weaknesses, setting long-term objectives, generating strategic alternatives, and selecting appropriate strategies. The school principal has demonstrated significant capability in fostering creative and innovative ideas, evidenced by achievements such as a third-place finish in the Madrasah Science Competition (KSM) at the district level. The implementation of strategic initiatives, including the "Adab-Based Curriculum Module" and literacy programs, reflects a collaborative and participatory approach involving all stakeholders. These initiatives not only enhance academic performance but also cultivate Islamic ethical values among students. Overall, the application of Fred R. David's strategic formulation theory underscores the effectiveness of strategic management in educational settings, emphasizing collaborative leadership and holistic development